PENGARUH LIVE STREAMING SELLING DAN DISCOUNT TERHADAP MINAT BELI TOKOH BELIA KOSMETIK PADA E-COMMERCE SHOPEE - Syaifudin Ma'arif; Esti Maulida Apriliana; Edita Rachma Kamila (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
Live Streaming Selling has become a dominant force shaping consumer Purchase Intention toward Tokoh Belia Cosmetics on the Shopee marketplace. The real-time demonstration of products, two-way communication, and visual proof of quality successfully build credibility and emotional involvement, leading viewers to feel more certain and willing to purchase during livestream sessions. Discount promotions also contribute positively to Purchase Intention, yet their effect remains statistically insignificant, suggesting that young cosmetic consumers do not rely solely on price reductions when deciding to buy. Product trust and authenticity conveyed through interactive broadcasting are perceived to be more valuable than temporary price incentives. The combination of both variables explains 88.6% of the variance in Purchase Intention, proving strong predictive power and high relevance for digital marketing strategies. These findings highlight that competitive advantages in the cosmetic industry within e-commerce ecosystems are more effectively achieved by optimizing persuasive livestream performance rather than focusing only on seasonal price promotions.